ABCG2 protein expression in tumors of patients with non-resectable pancreatic cancer treated with gemcitabine and nab-paclitaxel - Susy Shim; Susy Shim; Mette Bak Nielsen; Mikkel Eld; Jan Stenvang; Jan Stenvang; Rasmus Froberg Brøndum; Rasmus Froberg Brøndum; Britta Weber; Anne Krejbjerg Motavaf; Morten Ladekarl; Morten Ladekarl (Frontiers in Oncology)
BackgroundATP-binding cassette (ABC) proteins are transmembrane efflux pumps that play a role in Multi Drug Resistance. ABCG2 and ABCB1 have been suggested as important mediators of resistance to chemotherapy (CTx) in pancreatic cancer (PC). We determined the expression of ABCG2 and ABCB1 proteins in PC and the impact of ABCG2 on outcome of treatment with gemcitabine and nab-paclitaxel (GemNab).Materials and methods140 patients with sufficient tissue for assessment that had initiated palliative treatment with GemNab for non-resectable PC from 2011 to 2019 were included at two institutions. From achieved tissue, new sections were cut and stained for ABCG2 and ABCB1. Staining was evaluated by consensus of maximum score by two pathologists. Progression-free survival (PFS) was the primary endpoint.ResultsABCB1 expression was observed in only one case (0.7%). ABCG2 was expressed in 33% but more frequently (50%) in specimens taken after gemcitabine-based (neo)adjuvant CTx (P=0.02). In multivariate analysis, ABCG2 expression was associated with an improved PFS (HR=0.64; 95%CI 0.43-0.94 (P=0.02)) of treatment with GemNab. Prior CTx, both in the (neo)adjuvant and palliative setting, was associated with shorter PFS of GemNab (P=0.03), and ABCG2 expression tended to correlate with improved PFS in these (P=0.07), but not in CTx-naïve patients (P=0.20). Similarly, a high ABCG2 expression was associated with improved overall survival (OS) only in patients with prior exposure to CTx (P=0.03). No associations of ABCG2 expression with CTx dosing or response rates were found.ConclusionWe found indications of upregulation of ABCG2 expression in tumors of patients previously exposed to gemcitabine, and ABCG2 expression correlated with efficacy of GemNab as assessed by PFS and OS in patients previously exposed to CTx, but not in those naïve to CTx. These findings diverge from the prevailing assumption that ABCG2 confers chemoresistance and suggest that in certain contexts, ABCG2 expression may reflect tumor adaptation or selection. Given the unexpected direction of this association, our findings should be interpreted as hypothesis-generating, and further studies are needed to elucidate underlying biological mechanisms and validate ABCG2 as a potential predictive biomarker in this setting.